2016
DOI: 10.1126/scisignal.aaf6530
|View full text |Cite
|
Sign up to set email alerts
|

Stem-piped light activates phytochrome B to trigger light responses in Arabidopsis thaliana roots

Abstract: The roles of photoreceptors and their associated signaling mechanisms have been extensively studied in plant photomorphogenesis with a major focus on the photoresponses of the shoot system. Accumulating evidence indicates that light also influences root growth and development through the light-induced release of signaling molecules that travel from the shoot to the root. We explored whether aboveground light directly influences the root system of Arabidopsis thaliana Light was efficiently conducted through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 43 publications
7
131
0
2
Order By: Relevance
“…Light piping is wavelength specific, and long wavelengths such as FR and near infrared light are transmitted relatively well, while shorter wavelengths such as blue and green light are less effectively transmitted (Sun et al, 2003(Sun et al, , 2005. Stem-piped light can activate root-expressed phyB, which on its turn regulates HY5 in the Arabidopsis root (Lee et al, 2016). HY5 is involved in root growth in response to light, modulating, for example, root gravitropism and nitrogen uptake (Cluis et al, 2004;Lee et al, 2007;Huang et al, 2015;Chen et al, 2016).…”
Section: Stem-piped Lightmentioning
confidence: 99%
“…Light piping is wavelength specific, and long wavelengths such as FR and near infrared light are transmitted relatively well, while shorter wavelengths such as blue and green light are less effectively transmitted (Sun et al, 2003(Sun et al, , 2005. Stem-piped light can activate root-expressed phyB, which on its turn regulates HY5 in the Arabidopsis root (Lee et al, 2016). HY5 is involved in root growth in response to light, modulating, for example, root gravitropism and nitrogen uptake (Cluis et al, 2004;Lee et al, 2007;Huang et al, 2015;Chen et al, 2016).…”
Section: Stem-piped Lightmentioning
confidence: 99%
“…3D). In addition to HY5 being a traveling molecule, another recent study showed that its stability and transcription are induced by stem-piped light that locally activates PHYB molecules in the Arabidopsis roots (Lee et al, 2016). Besides auxin and HY5, sugar molecules travel from the light-exposed cotyledons, which started photosynthesis, to the roots and enhance root elongation (Kircher and Schopfer, 2012; Fig.…”
Section: The Rootsmentioning
confidence: 99%
“…These results can be explained by the impairment of root elongation and phytochrome involvement in root development. In fact, it has been observed that phytochromes triggered the expression of ELONGATION HYPOCOTYLS 5 (HY5) and, in turn, the HY5 protein acted as a transcription factor and promoted root growth in response to light (Lee et al 2016). In addition, it was verified that plants treated with Cd exhibited an enlargement of the roots and a reduction in root elongation (Fusconi et al 2007;Maksimovic et al 2007).…”
Section: Resultsmentioning
confidence: 99%